The Role of Environmental Law in Encouraging Climate Adaptation Towards Net Zero Emissions in Indonesia - Romulus, ‎ (KnE Social Sciences, 2025)
Climate change is a global challenge caused by human activities and has a broad impact on social, economic, and ecosystem life. In Indonesia, the increasing frequency of natural disasters is clear evidence of the impact of climate change that needs to be responded to immediately through adaptive and equitable legal policies. This research aims to analyze the implementation of environmental law in supporting climate adaptation and achieving the Net Zero Emission (NZE) target. The method used is a qualitative approach through literature study and regulatory analysis. The results show that although Indonesia has a relatively comprehensive legal framework, such as Law No. 32/2009 and its implementing regulations, implementation still faces various structural challenges, including weak law enforcement, overlapping authorities, limited low-carbon technology, and low public participation. In addition, policies such as carbon tax and carbon trading have not run optimally due to weak coordination and resistance from industry players. Therefore, an integrative strategy is needed through strengthening institutional capacity, green economy incentives, increasing environmental literacy, and developing domestic technology. Consistent, participatory, and justice-based law enforcement is the main foundation for Indonesia’s transition to sustainable development and climate resilience.